Lung Function Test among Abrasive Blasting Workers in Lumut, Perak - Zakaria, Hanis; Fauzy, Muhammad Faris; Sies, Mohamad Farid; Mat, Mohamad Nur Hidayat; Hassan, Suhaimi; Asmuin, Norzelawati (International Journal of Integrated Engineering, 2019)
Abrasive blasting process is a common process in marine industry. This process was use as main cleaning process method and normally will release fine dust that hazardous to human health. Main effect from fine dust to human health are respiratory failure such as chronic obstructive pulmonary disease (COPD). Lung function test can be used to detect any respiratory problems in human. The objective of the research to evaluate the effect of dust exposure from abrasive blasting to the workers. This study are conduct among workers work in dusty environment in Lumut, Perak, Malaysia. FEV1/FVC value from lung function test were evaluated to determine the severity of COPD among workers. While FEV1 prediction show restrictive pattern and use to determine any respiratory or lung problems among the workers. From the result, it does not show any COPD problem among workers. However, FEV1 show that some workers need to go for detail medical surveillance because of the result is less than 0.8. Employer and workers need to understand and know their work related risk to minimize the risk arising from their job or work conducted.